Ecological hazard, typology, morphometry and quantity of waste dumps of coal mines in Ukraine - Zubov, Anton; Zubov, Aleksei`; Zubova, Liliya (Ecological Questions, 2023)
As a result of coal mining, a large number of waste rock dumps have been created on the earth's surface around the world. As a result of deflation and water erosion of the dump surface, extensive contamination of the soil cover of agricultural land with heavy metals occurs, threatening the food security of many countries. The article proposes a method for determining the area of potentially contaminated land in coal-mining regions. The area of such land in Ukraine has been estimated. A scheme for the dispersion of pollutants from waste dumps is proposed, which makes it possible to identify four types of polluted areas. Using the Google Earth service, the exact modern number of dumps in the Donetsk coal basin (Donbass) as a whole (1600) and separately in its western, central and eastern parts was determined. The average height, the average and total area of the base and surface, and the forest cover of the dumps in the Central Donbass were determined. It was found that the area of potentially contaminated land as a result of surface deflation of dumps in Central Donbass is 30,605 hectares. Taking into account the discharge of pollutants both from the surface of the dumps and from the deflationary pollution zone, the area of such land is 35,765 hectares. The mathematical modelling of the processes of pollutant removal by wind and deposition on the soil surface showed that it is possible to radically reduce the area of pollution by afforestation of waste dumps and, first of all, their flat tops.